2018
DOI: 10.1097/jom.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Health and Fitness Benefits But Low Adherence Rate

Abstract: Although a structured on-site physical activity program supports improved health indicators, adherence remains a concern and requires specialists to develop new strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Strategies that aim at breaking this sedentary time must also be conducted. Recent data have shown that among office workers, who spend at least 7 h per day seated at their desk mostly in front of a screen, health indicators such as waist circumference, body mass index, or fat mass are not improved among active employees compared to inactive ones, suggesting the potential negative impact of sedentary time over physical activity levels ( 29 ). These results are of particular importance and are associated with recommendations formulated by Rosenberg et al calling for interventions targeting high-risk populations, such as tertiary employees ( 30 ).…”
Section: Sedentary Behaviors and Physical Activity: Implications In Omentioning
confidence: 99%
“…Strategies that aim at breaking this sedentary time must also be conducted. Recent data have shown that among office workers, who spend at least 7 h per day seated at their desk mostly in front of a screen, health indicators such as waist circumference, body mass index, or fat mass are not improved among active employees compared to inactive ones, suggesting the potential negative impact of sedentary time over physical activity levels ( 29 ). These results are of particular importance and are associated with recommendations formulated by Rosenberg et al calling for interventions targeting high-risk populations, such as tertiary employees ( 30 ).…”
Section: Sedentary Behaviors and Physical Activity: Implications In Omentioning
confidence: 99%
“…7 Strategies have been implemented in tertiary companies, such as onsite PA programs, to improve workers' health. 8 Although those programs specifically engaged people meeting the PA recommendations, it has been shown that being physically active could be insufficient to prevent the deleterious effects of SB, 3 raising the need for interventions to also decrease sedentary time (ST) during working days. Recently, active workstations have been promoted as potential strategies to reduce ST, while increasing PA with associated positive health effects.…”
mentioning
confidence: 99%
“…Our team has previously described an important dropout rate during worksite programs that proposed on-site PA during non-working hours among office workers [ 108 ]. By contrast, this study is an interventional study, and subjects will be monitored and motivated individually every day by receiving reminders (if time spent cycling < 60 min/day) and an on-site personal visit each week.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of adherence to programs aiming at increasing PA in tertiary employees has been reported multiple times [ 107 , 108 ]. Genin et al postulated that interventions targeting PA and SB in tertiary employees should not only consider the operational feasibility but also the coherence and compatibility with the working environment, structuration, functioning as well as the workers and the way they live and experience their work [ 24 ].…”
Section: Methods and Analysismentioning
confidence: 99%